If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-1=(5P+3P)-8
We move all terms to the left:
-1-((5P+3P)-8)=0
We add all the numbers together, and all the variables
-((+8P)-8)-1=0
We calculate terms in parentheses: -((+8P)-8), so:We get rid of parentheses
(+8P)-8
We get rid of parentheses
8P-8
Back to the equation:
-(8P-8)
-8P+8-1=0
We add all the numbers together, and all the variables
-8P+7=0
We move all terms containing P to the left, all other terms to the right
-8P=-7
P=-7/-8
P=7/8
| 8(x-9)=96 | | 16f-24=16+56f | | 5x-3=3/8x-3 | | 13.27=37.72-n | | 3-b2=13 | | 4x+13=5x+15 | | V+44=2v | | X+0.16x=4500 | | 3x+7=10x+50 | | 17=7z+3 | | 1/4z-2/7=5.7 | | 4x+6x+8=18 | | 2=-2+4w | | X=3x=14-4 | | 1.2x-8=4.4 | | 12s-17=5s+74 | | 4+u/5=-31 | | _4×+y=_19_4 | | -n+12=3n-8 | | 1.1x+10=16.6 | | 4v-1=6v-10 | | 3u-4=4u-5 | | 3u+4=4u-5 | | -8k−8=8k+8 | | Y=3.5x+100 | | 7-3x+2=-8x-8 | | 20=6-6n+8 | | 4x^2-16x-25=0 | | 16/21=6/x | | 4(6c+1)-18=22c+4 | | 8=4x+2-x | | 4t2–9t+9=0 |